The Role of Customer Value and Customer Pride as Variable Mediation on Customer Engagement Relationship with Corporate Image - Panjaitan, Hotman; Komari, Ana (International Review of Management and Marketing, 2018)
The purpose of this research is to find clarity about the role of customer value and customer pride as mediation variable on customer relationship engagement with corporate image, by designing and forming one research model. The research approach is quantitative, explanatory. The population of this research is the student at 5 best private universities in Surabaya. The sample of research was 250 respondents determined by using non-probability and purposive sampling method. Analytical technique using Structural Equation Model with Amos analysis tool. The results showed that the research model was accepted with the coefficient of determinant (R2) of 80.6%. The research also shows the clarity that: Customer engagement positively affect customer value, customer pride, and positively insignificant effect on corporate image. Customer value positively influences corporate image. Customer pride positively affect the corporate image. The results also explain that: customer value acts as a positive mediation on customer engagement relationship with corporate image, and Customer pride acts as a positive mediation on customer engagement relationship with corporate image Keywords: customer engagement, customer value, customer pride, corporate image JEL Classifications: M1, M3 https://doi.org/10.32479/irmm.6808